Pengaruh umur larva terhadap kualitas ratu yang dihasilkan pada penangkaran lebah ratu Apis cerana L. (Hymenoptera: Apidae) dengan teknik pencangkokan - Kuntadi Kuntadi (Jurnal Entomologi Indonesia, 2013)
An experimental study to find out the effect of larval ages to the quality of queens produced through queen-grafting technique has been done in Apis cerana colony. Each of four larval ages(1-4 day-old larvae) was grafted into 5 queen cups in every single colony. Five colonies were used in the study as experimental replications. Pupal weight was used as initial indicator of potential reproductivity of upcoming queen. The results showed that larval age affected both the acceptance rate of grafted larvae and queen pupal weight. The acceptance rate of young larvae was higher than old larvae as shown by their successful number of capped queen cells development. The mean number of capped queen cells developed from larvae at the age of 1, 2, 3, and 4 day-old were 4.4 ± 1.1 cells/colony, 3.4 ± 1.1 cells/colony, 2.0 ± 1.0 cells/colony, and 2.4 ± 0.5 cells/colony, respectively. The queens reared from 1 and 2 day-old larvae significantly had heavier pupae than those from both 3 and 4 day-old larvae. The mean pupal weight grafted from 1, 2, 3 day, and 4 day old larvae were 153.33 ± 4.48 mg/pupae, 149.14 ± 6.29 mg/pupae, 126.17 ± 7.28 mg/pupae, and 126.70 ± 7.61 mg/pupae, respectively. There were no differences between pupal weight grafted from 1 and 2 day-old larvae and between pupal weight grafted from 3 and 4 day-old larvae. The study showed that 1 and 2 day-old grafted larvae potentialy produced better quality queens than those of older larvae.